Anzac Biscuits - A Culinary Memorial - Supski, Sian (API Network, 2006)
Anzac biscuits form an integral part of commemoration of the Anzac tradition in Australia. Symons (1982) argues that Anzac biscuits may be regarded as only one of two distinctly Australian foods. Inglis (1998) does not mention them in his work on memorials, yet it is possible to argue that Anzac biscuits may be regarded as a culinary memorial (Hillier 2002).The story of Anzac biscuits has become mythologised in Australian cultural history and is an important signifier of Australian national identity. However, the origin of Anzac biscuits is contested, in particular the 'moment' of invention, including the naming and origin of the recipe. Moreover, Anzac biscuits have such a central place in the Australian public memory that it is not necessary to gain permission from the Minister of Defence to use the word 'Anzac' in relation to Anzac biscuits (Topperwien 1997).This paper seeks to propose that Anzac biscuits are a culinary memorial, that they represent a lasting commemoration of the Anzac spirit. Through an examination of a number of texts, including cookbooks and recipes, I will argue that Anzac biscuits represent a unique window into exploring Australian national identity and public memory.